The Impact of Culture on Reactions to Promise Breaches: Differences Between East and West in Behavioral Integrity Perceptions. Issue 2 (April 2018) - Friedman, Ray; Hong, Ying-Yi; Simons, Tony; Chi, Shu-Cheng (Steve); Oh, Se-Hyung (David); Lachowicz, Mark
Behavioral integrity (BI)—a perception that a person acts in ways that are consistent with their words—has been shown to have an impact on many areas of work life. However, there have been few studies of BI in Eastern cultural contexts. Differences in communication style and the nature of hierarchical relationships suggest that spoken commitments are interpreted differently in the East and the West. We performed three scenario-based experiments that look at response to word–deed inconsistency in different cultures. The experiments show that Indians, Koreans, and Taiwanese do not as readily revise BI downward following a broken promise as do Americans (Study 1), that the U.S.–Indian difference is especially pronounced when the speaker is a boss rather than a subordinate (Study 2), and that people exposed to both cultures adjust perceptions of BI based on the cultural context of where the speaking occurs (Study 3).